Valorizing staple Native American food plants as a food resilience resource - Winstead, Daniel J.; Jacobson, Michael G.; Di Gioia, Francesco (Frontiers in Sustainable Food Systems, 2023)
Increased risks from global climate change and sun-blocking global catastrophic risks (such as a nuclear winter), warrant the reevaluation of our food systems and their resilience to these climatic changes. The United States has shown little systematic effort to improve its agrobiodiversity, which is an easy way of increasing food system resilience, despite the vast amount of native genetic resources available in North America. In this study we use a systematic literature review of 174 staple Native American food plants (NAFPs) to determine the current state of research interest among them and suggest species of interest for domestication. The nutrient profiles and nutrient adequacy scores for the most researched staple NAFPs were collected and calculated. Using this information, we discuss potential actions, protocols, and ethical issues regarding future steps in using NAFPs to increase agrobiodiversity and food resilience in the United States through more resilient agroforestry systems.